Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0093
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Nitrosoarenes with SH Groups

Abstract: Introduction and Historical Remarks Reaction Products and Pathways Biological Significance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 146 publications
1
8
0
Order By: Relevance
“…C-Oxidation yielding phenolic metabolites is generally involved in the detoxification process. However, aminophenols can be metabolized to reactive iminoquinones . Acetylases and deacetylases (DAC) have an important role in the metabolism of arylamines.…”
Section: Metabolism Of Arylamines and Nitroarenesmentioning
confidence: 99%
See 2 more Smart Citations
“…C-Oxidation yielding phenolic metabolites is generally involved in the detoxification process. However, aminophenols can be metabolized to reactive iminoquinones . Acetylases and deacetylases (DAC) have an important role in the metabolism of arylamines.…”
Section: Metabolism Of Arylamines and Nitroarenesmentioning
confidence: 99%
“…Lotlikar et al found that nitrosofluorene forms hydrolyzable adducts with cysteine of peptides . Eyer , and Neumann , studied the adduct formation of nitrosoarenes with GSH and Hb in erythrocytes (Figure ). N -Hydroxyarylamines are oxidized in the erythrocytes to nitrosoarenes, which form semimercaptals with the thiol group of cysteine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…186 According to our current knowledge of arylamine adduct formation, the hydrolyzable fraction is derived from the reaction products of the arylnitrosoderivatives yielding aryl sulfinamide adducts with cysteine. 53,187 The nonhydrolyzable fraction probably results from the reaction products of activated N-hydroxyarylamines or their nitrenium/ carbenium ion species with other amino acids. Protein adducts formed with nitrosoarenes are generally higher with Hb than with PP.…”
Section: Albumin Adducts Formed With Toxicantsmentioning
confidence: 99%
“…52 The reactivity of Hb with aromatic amines and production of methemoglobin by genotoxic arylhydroxylamines has also been well studied and reviewed. 53,54 Pereira et al showed a linear relationship between Hb-adducts and DNA-adducts for 2-acetylaminofluorene in mice and rats. 55 Hb adduct formation for many aromatic amines occurs as a sulfinamide linkage formed by reaction of the arylnitroso intermediates with the β-Cys 93 chain of Hb.…”
Section: Introduction To Human Biomonitoring and History Of Protein A...mentioning
confidence: 99%